Pharmacologically significant constituents collectively responsible for anti-sepsis action of XueBiJing, a Chinese herb-based intravenous formulation - Cheng Chen; Ren Chao; Li Mu-zi; Liu Yi-hui; Yao Ren-qi; Yu Yang; Yu Xuan; Wang Jian-li; Wang Li-xue; Leng Yu-chun; Zhang Hui; Du Fei-fei; et al. (Acta Pharmacologica Sinica, 2024)
Sepsis, a life-threatening health issue, lacks effective medicine targeting the septic response. In China, treatment combining the intravenous herbal medicine XueBiJing with conventional procedures reduces the 28-day mortality of critically ill patients by modulating septic response. In this study, we identified the combined active constituents that are responsible for the XueBiJing’s anti-sepsis action. Sepsis was induced in rats by cecal ligation and puncture (CLP). The compounds were identified based on their systemic exposure levels and anti-sepsis activities in CLP rats that were given an intravenous bolus dose of XueBiJing. Furthermore, the identified compounds in combination were assessed, by comparing with XueBiJing, for levels of primary therapeutic outcome, pharmacokinetic equivalence, and pharmacokinetic compatibility. We showed that a total of 12 XueBiJing compounds, unchanged or metabolized, circulated with significant systemic exposure in CLP rats that received XueBiJing. Among these compounds, hydroxysafflor yellow A, paeoniflorin, oxypaeoniflorin, albiflorin, senkyunolide I, and tanshinol displayed significant anti-sepsis activities, which involved regulating immune responses, inhibiting excessive inflammation, modulating hemostasis, and improving organ function. A combination of the six compounds, with the same respective doses as in XueBiJing, displayed percentage survival and systemic exposure in CLP rats similar to those by XueBiJing. Both the combination and XueBiJing showed high degrees of pharmacokinetic compatibility regarding interactions among the six active compounds and influences of other circulating XueBiJing compounds. The identification of XueBiJing’s pharmacologically significant constituents supports the medicine’s anti-sepsis use and provides insights into a polypharmacology-based approach to develop medicines for effective sepsis management.